Capital Structure Determinants During the Sovereign Debt Crisis Period - Krishna Reddy; Nawazish Mirza; Noel Yahanpath (Australasian Accounting, Business and Finance Journal, 2022)
This study investigates the speed of adjustment of capital structure of small and medium capitalised firms in Europe before and during the sovereign debt crisis period. The sample includes 306 firms from 10 European countries comprising 2,142 firm-year observations for the period 2006 to 2013. After controlling the influence of firm-level, industry-level, and macroeconomic factors on debt levels, we report that small and medium capitalised firms have adjusted their capital structure during the sovereign debt crisis period and the speed of adjustment was quicker in non-stressed countries compared to the firms in the stressed countries. Our findings also show that the quality of countries’ institutional factors has significantly influenced the speed of adjustment of leverage of small and medium capitalised firms during the crisis period. Our findings suggest that the firm-level determinants of leverage for small and medium capitalised firms in Europe are; size and asset tangibility. Furthermore, the industry-level determinant is industry median leverage and macroeconomic-level determinants are GDP growth rate and inflation rate. The policy implications of the findings indicate that improving the country’s institutional environment (such as governance, rule of law, and corruption) will ease small and medium capitalised firms’ financial difficulties, which in turn facilitate their economic performance and resilience.
Keywords: Leverage; small and medium capitalised firms; capital structure; sovereign debt crisis; stressed country; non-stressed country